Judicial federalism in the United States: structure, jurisdiction and operation - Tarr, G. Alan (Revista de Investigações Constitucionais, 2015)
The present article aims to analyze the judicial federalism in the United States. To do so, it compares the jurisdiction and the autonomy of the federal and states courts, concluding that the model adopted in the Judiciary is similar to that followed by the Executive and Legislative branches. Furthermore, it analyzes the federalization of Criminal Law, affirming that, in this field, the defendants have the right to appeal to federal courts every time that some damage has been caused to them based on a state law, violating a federal law. By the end, it concludes that, despite the existence of some endemic and periodical problems, the American system of judicial federalism has largely succeeded in promoting national uniformity and subnational diversity in the administration of justice.